A study on evaluation of sino-nasal outcome test-22 scores in chronic rhinosinusitis patients undergoing functional endoscopic sinus surgery in a tertiary care centre - Santhaiah, Kakumanu; Kornepati, Lavanya Lakshmi; Devi, Pindiprolu Kameswari (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Chronic rhinosinusitis (CRS) is defined as an inflammation of the nose and paranasal sinuses and is characterized by two or more cardinal symptoms like nasal blockage/obstruction/congestion, nasal discharge (anterior/posterior nasal drip), facial pain/ pressure, reduction or loss of smell. Methods: The 55 patients diagnosed with CRS with and without nasal polyps undergoing functional endoscopic sinus surgery were included in this study, whose sino-nasal outcome test 22 (SNOT-22) scores were compared both pre operatively and post op, 3 months after functional endoscopic sinus surgery. Results: Total score of SNOT-22 was significantly lower in CRS patients post-operatively when compared to pre-operative score of SNOT-22 (p<0.0001). Conclusions: Functional endoscopic sinus surgery effectively improved quality of life of patients with CRS.